THE MEDIATING ROLE OF FINANCIAL LITERACY AND FINANCIAL RISK TOLERANCE IN PARENTAL FINANCIAL TEACHING ON FINANCIAL ATTITUDES OF BUY NOW PAY LATER USERS IN GENERATION Z IN INDONESIA - Septania, Tamara; Gosal, Gladys Greselda (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This research examines the intermediary roles of financial literacy and financial risk tolerance in the connection between parental financial teaching and the financial attitudes of Generation Z users of Buy Now Pay Later (BNPL) services in Indonesia. The study analyzed data from 199 respondents aged 18 to 26, using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that parental financial teaching significantly affects financial literacy, risk tolerance, and financial attitudes. Financial literacy was found to mediate the influence of parental teaching on financial attitudes, highlighting its essential role in fostering responsible financial behaviors. Conversely, financial risk tolerance did not demonstrate a significant mediating role, suggesting limited awareness of the risks tied to BNPL usage. These outcomes emphasize the importance of parental financial education and financial literacy in encouraging prudent financial behaviors. The study underscores the urgent need for targeted financial education to promote responsible BNPL usage among young adults.